THE EFFECT OF STOCK OWNERSHIP AND DIVIDEND POLICY ON EARNINGS QUALITY IN COMPANIES LISTED ON THE JAKARTA ISLAMIC INDEX - Oki Sania Riski; Rika Lidyah; Titin Hartini (Journal of Business Studies and Management Review, 2021)
This study aims to determine the effect of stock ownership and dividend policy on earnings quality in companies listed on the Jakarta Islamic Index. This study uses a quantitative research method and uses panel data, combining time-series and cross-sectional data. The samples used in this study were eight companies registered in the Jakarta Islamic Index from 2015 to 2019. The data analysis technique in this study is multiple regression analysis using the SPSS 22 application. The results in this study indicate that partially institutional ownership has a significant effect on earnings quality, managerial ownership has a significant effect on the quality, and dividend policy has no effect on earnings quality.